Relevant issues regarding the establishment of domestic vegetables gardens through the use of biodegradable solid wastes as a fertilizer source - Campos-Rodríguez, Rooel (2016)
Guacimo´s Local Government developed studies in the past concerning solid waste management in its area of influence, but lacks of specific actions oriented to using of biodegradable solid wastes. This article relates to knowledge, mind-set and behavior of a studied sample of individuals from Guácimo regarding to the use of biodegradable solid wastes in the establishment of domestic vegetables gardens, and the barriers they find to improve it. The result shows an intention from Guacimo´s inhabitants to use solid wastes and establish vegetables gardens in their homes, and their disposition to acquire knowledge or redefine their prior one, as well as to modify their behaviors, to surpass existing barriers and to develop actions driven towards environmental preservation.